Comparative Analytical Study of Phytochemicals in Selected Antidiabetic Medicinal Plant Seeds in Sri Lanka - Rajkumar, Gowri; Jayasinghe, Mihiri Rangika; Sanmugarajah, Vinotha (Pharmaceutical Sciences and Research, 2021)
Medicinal plants are universally used in the management of various diseases in different medical practices. A varied diversity of compounds extracted from plants may show anticancer, antibacterial, and antidiabetic activities. Comparative laboratory studies and scientific approach of efficacy related to phytochemicals found in medicinal plants in Sri Lanka have not been reported yet. This study aims to evaluate the phytochemicals in selected four different plant seeds such as Syzygium cumini (L.) Skeels, Brassica alba (L.) Rabenh, Trigonella foenum-graecum L. and Nigella sativa L., which are used in the management of diabetes mellitus in Sri Lanka. The ethanol extracts of plant seeds were subjected to the qualitative and quantitative analysis of the phytochemicals using recommended laboratory techniques. Data were analyzed by Analysis of Variance using a Statistical Analysis System (SAS) statistical package. The qualitative analysis showed that flavonoids, tannins, phenols, alkaloids, and saponins were present in all medicinal seed extracts. Based on quantitative analysis, flavonoids were found in all seed extracts, and higher amount was found in S. cumini (527.77 µg QE/g) followed by T. foenum-graecum (194.66 µg QE/g). S. cumini seeds contain higher phenolics (416.01 µg GAE/g), alkaloids (81.07 mg/g), and tannins (34.04 µg TAE/g) contents than other seed extracts. This study revealed that all these medicinal seeds, especially S. cumini, has potential as prepared standard functional products in the traditional system of medicine.